Prostate-specific membrane antigen modulates the progression of prostate cancer by regulating the synthesis of arginine and proline and the expression of androgen receptors and Fos proto-oncogenes. Issue 1 (1st January 2022) - Hong, Xi; Mao, Liang; Xu, Luwei; Hu, Qiang; Jia, Ruipeng
ABSTRACT: The expression of prostate-specific membrane antigen (PSMA) is strikingly upregulated during oncogenesis and prostate cancer (PCa) progression, but the functions of this antigen in PCa remain unclear. Here, we constructed PSMA-knockdown LNCaP and 22rv1 cell lines and performed metabonomic and transcriptomic analyses to determine the effects of PSMA on PCa metabolism and transcription. The metabolism of arginine and proline was detected using specific kits. The mRNA and protein expression levels of the identified differentially expressed genes were quantified by RT-qPCR and Western blotting. The proliferation of each cell line was evaluated through CCK-8, EdU and colony formation assays. The migration and invasion abilities of each cell line were detected using wound healing and transwell assays, respectively. PSMA knockdown led to metabolic disorder and abnormal transcription in PCa and resulted in inhibition of the proliferation and metastasis of PCa cells in vitro and in vivo. The depletion of PSMA also promoted the biosynthesis of arginine and proline, inhibited the expression of AR and PSA, and induced the expression of c-Fos and FosB. PSMA plays an important role in the metabolism, proliferation and metastasis of human PCa and may be a promising therapeutic target.